Methemoglobin in Chironomus Larvae as Potential Biomarker of Nitrate Contamination in Water - Khazenzi, Judith A.; Wakhisi , Johnstone; Osano , Odipo; Raburu , Phillip (African Journal of Education,Science and Technology (AJEST), 2025)
Nitrate contamination of groundwater and surface water has been found to be high in various areas. Nitrates are known to have health impacts if consumed in different concentrations. The study set out to investigate the potential of using methemoglobin within chironomid larva e as a biomarker for nitrates in water. The ubiquitous and hemoglobin – containing chironomid larvae from Lake Victoria basin were identified using morphological characteristics and Chironomuswas found to bethe most common genera. The larvae can also withstand polluted waters. The Chironomus was therefore chosen for the study and was exposed to different concentrations of nitrate in water in the laboratory. The Chironomus larvae were analyzed for methemoglobin using a spectrophotometer and the levels compar ed to the exposure nitrate concentration of the test solution. Acute toxicity test was carried out by exposing the larvae to different concentrations of nitrate and determining the LC 50. Results showed a positive correlation between nitrate concentration and hemoglobin absorbance in the tested cases. The LC 50 after 48hrs was found to be 34.2 (30-39; 95% confidence limit) mgL-1 NO3-N for third instar larvae and for first instar larvae after 96hrs was 41.3 (35.9-50.0; 95% confidence limit) mgL- 1 NO3-N. From the results it can be seen that chironomid larvae have the potential to be used to indicate differences in nitrate concentration in water containing nitrate concentrations of upto 40 mgL-1 NO3-N. The study can help in the development of a bioassessment tool for nitrates in water. However, further work needs to be carried out on effect of age of the larvae on methemoglobin formation.